2015
DOI: 10.1111/bjd.13930
|View full text |Cite
|
Sign up to set email alerts
|

Levels and function of regulatory T cells in patients with polymorphic light eruption: relation to photohardening

Abstract: SummaryBackgroundWe hypothesized that regulatory T cells (Tregs) are involved in the immunological abnormalities seen in patients with polymorphic light eruption (PLE).ObjectivesTo investigate the number and suppressive function of peripheral Tregs in patients with PLE compared with healthy controls.MethodsBlood sampling was done in 30 patients with PLE [seeking or not seeking 311-nm ultraviolet (UV)B photohardening] as well as 19 healthy controls at two time points: TP1, March to June (before phototherapy); a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 52 publications
0
49
2
1
Order By: Relevance
“…Recent studies have also implicated UVR in the maintenance of a pool of B-regulatory cells in the periphery that can prevent an autoimmune attack on the CNS (55). Narrow band UVB irradiation can also increase peripheral T-regulatory cell numbers and their suppressive function in patients with polymorphic light eruption (56). …”
Section: Proposed Mechanism Of Prevention Of Ms Development By Uvb Phmentioning
confidence: 99%
“…Recent studies have also implicated UVR in the maintenance of a pool of B-regulatory cells in the periphery that can prevent an autoimmune attack on the CNS (55). Narrow band UVB irradiation can also increase peripheral T-regulatory cell numbers and their suppressive function in patients with polymorphic light eruption (56). …”
Section: Proposed Mechanism Of Prevention Of Ms Development By Uvb Phmentioning
confidence: 99%
“…We do know that PDCs cells can promote the generation, survival and expansion of Tregs through indoleamine 2,3 dioxygenase (IDO) and enhanced inducible costimulator ligand (ICOS‐L) and IDO expression by PDCs is binded to Tregs presence . According to that and recent results, we could assert that PLE patients may have a normal to higher number of PDCs and FOXP3+ CD4+ cells in front of an impaired suppressory function. The reason why Tregs in PLE patients have suboptimal suppressor capabilities is still unknown.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have investigated Tregs distribution and activity in patients affected by PLE. Schweintzger and coll . demonstrated that medical photohardening with 311‐nm UVB increases the number of Tregs in the blood of PLE patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although UVR immunosuppression is a hallmark of normal skin, impaired immunosuppression has been postulated to result in a reaction to UVR‐induced neoantigens eventuating in the development of clinical lesions. Photohardening appears to improve this initial dysregulation by causing regulatory T‐cell proliferation that promotes immunotolerance …”
Section: Immune‐mediated Photodermatosesmentioning
confidence: 99%